ANNUAL REPORT ON THE WORK OF THE CENTRAL INLAND FISHERIES RESEARCH STATION FOR THE YEAR 1952-53 - Mandapam, Central Marine Fisheries Research Statio (Indian Journal of Fisheries, 2016)
THE main work of this section is to solve the numerous difficulties and problems of the practical pisciculturist with a -view to aid him in producing the maximum amount offish as food with the minimum of expenditure. Fish seed" or fry of major carps have to be collected every year from rivers in the rainy season, conditioned and fed in suitable nurseries until they are fit to be transported to ponds, tanks and reservoirs, where they are grown until marketable.